2020
DOI: 10.37604/jmsb.v2i2.60
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biocarrier of Aspergillus niger and Trichoderma harzianum toward vegetative growth of sorghum in the field experiment

Abstract: Compared to other cereal crops, sorghum has a higher drought tolerance trait. However, efforts are needed to increase the productivity of sorghum, particularly in drought marginal land. One strategy to be implemented is the utilization of soil microorganisms formulated with biocarrier. Therefore, the aim of this study was to evaluate the influence of the fungal strain Aspergillus niger and Trichoderma harzianum formulated with compost and zeolite as biocarrier towards vegetative growth of sorghum. The field ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to previous research, bacteria have a role in hyphae growth and arbuscular mycorrhizal fungi's mycorrhizal ability on host plants [11,12]. There are bacteria and fungi in compost that can stimulate growth directly and increase plant growth through various mechanisms, including phosphate dissolution and the production of plant growth hormones such as auxins [13,14,15].…”
Section: Sterilization Treatmentsmentioning
confidence: 99%
“…According to previous research, bacteria have a role in hyphae growth and arbuscular mycorrhizal fungi's mycorrhizal ability on host plants [11,12]. There are bacteria and fungi in compost that can stimulate growth directly and increase plant growth through various mechanisms, including phosphate dissolution and the production of plant growth hormones such as auxins [13,14,15].…”
Section: Sterilization Treatmentsmentioning
confidence: 99%
“…Evidently, Trichoderma is applied in many kinds of cereal, such as Triticum aestivum L., Vigna radiata (L.) R. Wilczek and Sorghum bicolor shows an improved drought response by plants (Kaur & Kumar, 2020;Shukla et al, 2014;Sugiharto et al, 2020). Favorable activities ascribed to the Trichoderma-plant interactions include induced disease resistance, plant growth promotion, and tolerance to abiotic stresses (Harman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously reported that A. tubingensis , A. Niger , and A. Niger strains ITCB-09 exhibited a high capacity to dissolve inorganic phosphates, including through the production of organic acids [ 4 , 22 ]. In recent years, there have been many reports regarding the use of fungal microbial fertilizers; for example, to promote the vegetative growth of sorghum by inoculating soil with A. niger through means of bio-carriers [ 23 , 24 , 25 , 26 ]. Additionally, there have been reports of microorganisms that utilize fermentation processes to produce organic acids [ 27 ].…”
Section: Introductionmentioning
confidence: 99%